2018
DOI: 10.1016/j.artmed.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Handwritten dynamics assessment through convolutional neural networks: An application to Parkinson's disease identification

Abstract: The analysis of handwritten dynamics using deep learning techniques showed to be useful for automatic Parkinson's disease identification, as well as it can outperform handcrafted features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(70 citation statements)
references
References 31 publications
(42 reference statements)
2
58
1
2
Order By: Relevance
“…In both studies, time series data was used. In comparison to Pereira et al [35][36][37], our system showed consider gain in performance i.e. 80.19% [35], 90.38% [36], and 93.50 [37] to 98.28%.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In both studies, time series data was used. In comparison to Pereira et al [35][36][37], our system showed consider gain in performance i.e. 80.19% [35], 90.38% [36], and 93.50 [37] to 98.28%.…”
Section: Discussioncontrasting
confidence: 65%
“…Handwriting dataset has been used for detection of Parkinson's disease and provided effective results on BA approach with over all accuracy of 90.38% for spiral data. In 2018, Pereira et al [37] combined six representations ( spirals, drawing of circles on the page and in air, meanders, left-wrist and right-wrist movements) and extracted features by deploying CNN using pen based features (time series) from online images and reported about 93.50% accuracy. In both studies, time series data was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the diagnosis of Parkinson's disease, [17] introduced an improved and optimized version of the Crow Search Algorithm. Convolutional Neural Networks (CNN) were applied to hand-written exams to investigate their performance of PD detection, achieving 95% of accuracy [18].…”
Section: Related Workmentioning
confidence: 99%
“…The abovementioned work was extended by the authors in References [52,90]. In Reference [90], CNNs were used to learn features directly from time-series-based images. The main hypothesis was that texture-oriented features are able to encode the tremors during handwriting.…”
Section: Disease Diagnosismentioning
confidence: 99%